Violence exposure and burnout in healthcare sector: mediating role of work ability: il ruolo di mediazione della capacità lavorativa - Converso, Daniela; Sottimano, Ilaria; Balducci, Cristian (La Medicina del Lavoro, 2021)
Background: One of the most difficult problems faced by health care professionals is experiencing verbal and physical abuse from patients and their family members. Some studies have shown that health care workers, especially nurses, are up to 16 times more likely to be subject to violence than other workers. Aims: The aim of this study was to analyze the relationship between exposure to violence, work ability and burnout. Methods: Data were collected through a questionnaire to investigate health care workers’ exposure to violence (Violent Incident Form), burnout (Maslach Burnout Inventory) and work ability (Work Ability Index). A sample of 300 nurses was obtained for the study. Results: A total of 36% of nurses indicated that they had been a victim of violence in the past 12 months. The data analysis highlighted highly significant differences in work ability, emotional exhaustion and depersonalization between health care workers who had been victims of violence and those who had not experienced violence. Finally, work ability was shown to have a mediating effect on emotional exhaustion (indirect effect: b = 2.7, BCa CI: 1.37–4.33) and depersonalization (indirect effect: b = 1.1, BCa CI: 0.48–1.87). Discussion: This study is one of the first to consider the mediation effect of work ability between workplace violence experienced and burnout in the healthcare sector; it reports the complexity and severity of the consequences of workplace violence in this sector.